2021
DOI: 10.1097/mnm.0000000000001455
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of targeted single-photon emission computed tomography/computed tomography (SPECT/CT) bone scintigraphy on the assessment of bone metastasis in cancer patients

Abstract: Objectives We investigated the clinical impact of single-photon emission computed tomography/computed tomography (SPECT/CT) bone scintigraphy combined with 16-slice CT on metastatic workup and treatment planning in a large cancer patient series. Methods Between January 2019 and January 2020, a total of 600 cancer patients were prospectively evaluated with whole-body planar bone scan (wbPBS) for staging or restaging purposes. 272/600 had equivocal lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, their findings showed that WB-SPECT/CT had a diagnostic superiority over PBS. As a result, they recommended the WB-SPECT/CT protocol for all oncology patients [ 24 ]. However, the process was time-consuming as the acquisition time by 15–20 min per bed position.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, their findings showed that WB-SPECT/CT had a diagnostic superiority over PBS. As a result, they recommended the WB-SPECT/CT protocol for all oncology patients [ 24 ]. However, the process was time-consuming as the acquisition time by 15–20 min per bed position.…”
Section: Discussionmentioning
confidence: 99%
“…99 m Tc-labeled methylene diphosphonate ( 99 m Tc-MDP) whole-body scan (WBS) was frequently used in patients with bone lesions and had high sensitivity but low specificity. The radioactive tracer 99 m Tc-MDP was deposited in the bone by chemisorption and ion exchange, the abnormal uptake of the tracer reflected the osteogenic activity and local blood flow of the lesion ( 3 ). Single-Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) combined anatomic and metabolic functions to improve the accuracy of anatomic localization of lesions and the specificity of bone imaging ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%